Study on Left Ventricular Pacing: A Desperate Life-saving Measure in Emergency Situation - Ajaz Ahamad Lone; Mohd Iqbal Dar; Fayaz Ahamad Rather; Mohd Sultan Alai; Imran Hafiz; Jahangir Rashid Beigh (Highlights on Medicine and Medical Science Vol. 5, 2021)
In the cath lab, transcutaneous or transvenous pacing of the right ventricle is performed as a routine practise for patients with symptomatic bradycardia or complete heart block. Temporary transcutaneous or transvenous pacing is commonly the first intervention taught to cardiologists and intensivist, as it is one of the most important lifesaving interventions in cardiology. However, more and more patients are received with multiple comorbidities, critical condition, and difficult vascular access. The goal of this study is to report a patient who had challenging venous access, tricuspid regurgitation, and a displaced right ventricular pacemaker temporary lead who was handled with emergent nonconventional left ventricular pacing while having coronary angiography.